Pengaruh Annealing terhadap Sifat Keras dan Struktur Mikro Baja Tahan Karat AISI 410-3Mo-3Ni - Vinda Puspasari; Mukhlis Agung Prasetyo; Januarius Velix Ta’an Halab; Moch. Syaiful Anwar; Efendi Mabruri; Satrio Herbirowo (National Research and Innovation Agency (BRIN), 2020)
AISI 410-3Mo-3Ni stainless steel is a martensitic steel which limited in using when compared to austenitic and ferritic stainless steels. Martensitic steel has an essential role in specific components due to a combination of strength, toughness and excellent corrosion resistance. However, martensitic steel tends to undergo decreasing in mechanical properties and microstructure after the forging process. In this study, mechanical properties and microstructure of the forged AISI 410 after receiving annealing heat treatment will be studied. Annealing aims to reduce material hardness and increase grain refinement of material. Annealing heat treatment is carried out by varying the annealing temperature and time. Annealing temperature variations are 7000, 7600, and 8000C. The annealing time variation is 3 hours and 6 hours. The effect of annealing time and temperature will be studied on the hardness and microstructure of the AISI 410 modified material. The optimum hardness of 35.9 HRC in sample with annealing treatment in 760°C for 6 hours. The microstructure shows delta ferrite, martensite, austenite, and carbide phases which affect hardness value of annealed samples.